Spare parts warehouse re-layout design with kaizen 5S implementation to reduce wasted time searching for machine parts - Nuryono, Arif; Kurnia, Hibarkah; Zulkarnaen, Iskandar (Universitas Mercu Buana, 2023)
Increasing the productivity and efficiency of production machines cannot be separated from the availability of machine spare parts in the warehouse department. Delays in the delivery of spare parts if machine problems occur often become a problem that disrupts efficiency. This delay was caused by the search for engine spare parts in the warehouse taking too long to find. The long search time was caused by the irregular placement of the materials and the messy condition of the warehouse. This research aims to make improvements to the goods search process to make it faster and more effective in the warehouse area and increase warehouse capacity using warehouse re-layout. This research method uses the implementation of warehouse re-layouts combined with the application of Kaizen 5S in controlling the condition of machine spare parts. This research found that the reason for the long search time for machine spare parts was due to the lack of knowledge of warehouse operators and the absence of training regarding the application of the 5S method, as well as the careless placement of spare parts in warehouses that were not neatly arranged. This research has resulted in a reduction in search time for engine spare parts from 6.4 minutes to 4 minutes per spare part unit or a decrease of 36.5%. Meanwhile, the results of the warehouse re-layout resulted in an increase in warehouse capacity from 80 pallets to 316 pallets, an increase of 395%.